Social Movements and Socio-Political Transformation in Nepal (1950-2015) - Oli, Jagadish (Research Journal of Padmakanya Multiple Campus, 2025)
This paper examines how social movements contribute to the modification of sociopolitical structures in Nepal, particularly from anti-Rana movement (1950) to Madheshi movement (2015). The goal of the study is to present how the democratic and social movements have contributed to transferring the political and social structure of the state from the Rana regime to federal democratic Nepal. The study is based on qualitative research, including key informant interviews, case studies, and thematic analysis of information from both primary and secondary sources: scholarly articles, books and reports. Similarly, the study analyzes how social movements of Nepal can alter the lives of their people, particularly the Madheshi, Dalit, Janajati, Women, and Kamaiya. This study applies the theoretical perspectives of social movements, such as theories of social movements, political processes, and resource mobilization. These movements in Nepal have helped bring down the old regime and promote the adoption of democracy and a multi-party system, human rights, social inclusion, and proportional representation of marginalized and oppressed groups in the constitution's mainstream. The study concludes that social movements are both transformative and ongoing processes that foster the development of and establish democracy, human rights, and structural change in the country.